Impact of Cognitive and Affective Image on Tourists' Travel Motivation - Sabari Shankar, R. (Indian Journal of Marketing, 2020)
This empirical research paper was an extract from a major research work on understanding the image and personality of a destination. The research was conducted in Coimbatore – a potential and competing destination in Tamil Nadu, India between 2018 and 2019. Burgeoning global competition, emerging tourism-based business avenues, elevating foreign direct investments were the fundamental motives for this research. The objective of this research was to identify and validate a tourist motivation model inculcating the primitive factors such as destination image (cognitive and affective) and tourists’ motives to travel. Literature review found that perceived cognitive and affective image had a significant impact on the tourists’ travel motivation. Thus, these three factors were modeled conceptually. To validate the model, a structured questionnaire containing the necessary constructs measuring the required responses was floated to 570 tourists who visited the destination. However, the sample size was fixed to 448 after excluding the improper responses. Structural equation modeling was employed using SPSS AMOS software to validate the model hypothetically. The model fit was identified, and this study confirmed that both Cognitive Image and Affective Image had a significant impact on Tourists’ Travel Motivation. Destination marketers are suggested to formulate marketing strategies that induce the existing belief about the destination in tourists’ minds and experience being gained in the destination because belief and experience are related to motivation. Researchers are suggested to use this model as a base for further research by inculcating other constructs measuring the image aspects of the destination.